Implementasi Sistem Rujukan Terintegrasi (Sisrute) Puskesmas Dengan Rumah Sakit Sebagai Upaya Peningkatan Pelayanan Kesehatan Di Kabupaten Pamekasan - Della, Argitta; Talkah, Abu (Universitas Islam Kadiri, 2024)
Health service referrals are a form of health service delivery that regulatesthe delegation of duties and responsibilities for health services. Health servicereferrals start from primary health care and continue to secondary and tertiary service levels which can only be provided if there is a referral from primary or secondary health care. Referral to a higher level of health facility is called a tiered referral. Health referrals require fast, practical, efficient, accurate and reliable information. This research aims to determine the extent of the implementation of the Integrated Referral System (SISRUTE) in Pamekasan so that it can make it easier for health workers to optimize health services. The method used in this research was a qualitative approach. Data collection used Purposive Sampling with in-depth interview techniques through questions to 14 informants consisting of 10 nurses and 4 midwives accompanied by 1 Triangulator, head of the referral field for Pamekasan district. Data collection techniques use observation, interviews, documentation, and Foccus Group Discuss. The results of this research it is known that the Implementation of the Integrated Referral System (SISRUTE) in Pamekasan can help health workers speed up patient referrals with the help of supporting facilities and infrastructure as well as the ability of human resources to operate (SISRUTE)